Development and clinical application of hydrogel formulations containing papain and urea for wound healing - Thais Menezes dos Santos; Danieli Silva Feijó de Sousa; Karina Chamma Di Piero; Adriane Regina Todeschini; Wagner Barbosa Dias; Catarina Amorim Oliveira; Elisabete Pereira dos Santos; Mariana Sato de Souza Bustamante Monteiro; Maria Kátia Gomes; Cristiano dos Reis Moura; Pedro Antônio Castelo Teixeira; Eduardo Ricci-Junior; et al. (Universidade de São Paulo, 2023)
Abstract Hydrogels are used for wound treatment, as they may contain one or more active components and protect the wound bed. Papain is one of the active substances that have been used with this purpose, alongside urea. In this paper, carboxypolymethylene hydrogels containing papain (2% and 10% concentrations) and urea (5% concentration) were produced. Physical-chemical stability was performed at 0, 7, 15 and 30 days at 2-8ºC, 25ºC and 40ºC, as well as the rheological aspects and proteolytic activity of papain by gel electrophoresis. Clinical efficacy of the formulations in patients with lower limb ulcers was also evaluated in a prospective, single-center, randomized, double-blind and comparative clinical trial. The results showed 7-day stability for the formulations under 25ºC, in addition to approximately 100% and 15% of protein activity for 10% and 2% papain hydrogel, respectively. The rheological profile was non-Newtonian for the 10% papain hydrogel tested. There were no significant differences regarding the mean time for healing of the lesions, although 10% papain presented a better approach to be used in all types of tissue present in the wound bed.